(untitled) (European Journal of Economics, Finance and Business Development, 2024)
In the context of intense competition and globalization, the banking system faces the necessity of adopting innovative products and solutions to ensure sustainable development and enhance competitiveness. This article examines the key aspects of evaluating the effectiveness of implementing innovative products in the banking sector, focusing on both financial and qualitative indicators. Special attention is given to methods such as Net Present Value (NPV), Internal Rate of Return (IRR), and payback period, as well as the impact of innovations on improving customer experience and the bank’s reputation. Furthermore, the main risks associated with the introduction of innovations are analyzed, and recommendations for their mitigation are proposed. The conclusion emphasizes the importance of strategic innovation management to ensure the long-term sustainability and effectiveness of the bank.